Physicochemical and multitechnique characterisation of Structural, functional, optical, Thermal, Microbiological, Elemental, mechanical and Antibacterial properties of L-Asparagine monohydrate admixtured with Oxalic acid dihydrate with a focus on nonlinea - N. Rajasekar,; K. Balasubramanian, (The Bioscan, 2026)
L-Asparagine monohydrate admixtured with oxalic acid dihydrate (LASPOD) crystals were successfully grown and comprehensively analyzed to investigate their structural, optical, and thermal properties. Single crystals were obtained by the slow evaporation method under ambient conditions, yielding transparent and well shaped crystals. The crystallographic structure and unit cell parameters were derived from powder XRD. Powder XRD was employed to estimate the crystallite size and microstrain of L-Asparagine oxalic acid dihydrate, using the williamson-Hall (W-H) plot method to separate the contribution of crystallite size and strain.